An Exploring Consumer Preferences for University Merchandise: The Impact of University Identification, Product Attributes, Social Motivation, Purchasing Experience - Raden Rifqi Dwisanto (IHSA Institute, 2025)
This study examines the relationship between university identification, product attributes, social and psychological motivation, and purchasing experience with buyer preferences and purchase decisions regarding official Universitas Padjadjaran (Unpad) merchandise. Using the Spearman Rank Correlation method, data were collected from 23 respondents, including students, lecturers, and academic staff at Unpad. The findings indicate a positive and significant correlation between university identification and buyer preference, suggesting that merchandise serves as an identity symbol for students and alumni. Similarly, product attributes such as design, material quality, and exclusivity significantly influence purchasing preferences. Moreover, social and psychological motivation, including peer influence and emotional attachment, was found to be a strong predictor of merchandise preference. Additionally, customer experience in both physical stores and online platforms affected purchasing decisions, emphasizing the need for improved accessibility and service quality. The study highlights that buyer preference directly influences purchase decisions, reinforcing the role of branding, marketing strategies, and consumer engagement in university merchandise sales. The results provide strategic insights for enhancing Unpad’s merchandise marketing efforts, with implications for future research on university branding and consumer behavior in higher education institutions